2021
DOI: 10.1111/eva.13279
|View full text |Cite
|
Sign up to set email alerts
|

Density influences the heritability and genetic correlations of fish behaviour under trawling‐associated selection

Abstract: Harvest-associated selection is one of the most important humaninduced evolutionary pressures for natural populations (Darimont et al., 2015;Hendry et al., 2017). Phenotypic changes in life-history traits (such as reduced body size-at-age and/or earlier maturation) have been observed in many targeted populations, threatening their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This offers support for our results and indicates that stopping selection might not have hampered feeding behaviour. That said, it is possible that the observed variations among selection lines are due to other factors like density (Bouffet‐Halle et al 2021 ; Crespel et al 2021a , b ) and genetic drift (Therkildsen et al 2019 ). A recent study in medaka showed that life-history divergence may not be caused by direct harvest selection but by natural density-dependent selection for a larger body-size (Bouffet‐Halle et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This offers support for our results and indicates that stopping selection might not have hampered feeding behaviour. That said, it is possible that the observed variations among selection lines are due to other factors like density (Bouffet‐Halle et al 2021 ; Crespel et al 2021a , b ) and genetic drift (Therkildsen et al 2019 ). A recent study in medaka showed that life-history divergence may not be caused by direct harvest selection but by natural density-dependent selection for a larger body-size (Bouffet‐Halle et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though we maintained a uniform density of eight fish per box right from the embryonic stage and throughout the period of experiments, there could have been variations in fish density in the holding tanks during rearing and development. These differences in population developmental density may determine the evolutionary potential of size-selection (Crespel et al 2021a ). Further, genetic drift may cause differences between the selection line replicates (Therkildsen et al 2019 ) and this may account for the variations among selection lines.…”
Section: Discussionmentioning
confidence: 99%
“…While our knowledge on possible antagonistic evolutionary responses to harvesting increases, the role of demographic factors and impacts of adaptive evolution on the population dynamics remain poorly understood. In this special issue, Crespel et al ( 2021 ) undertook to experimentally simulate harvesting in groups of fish kept at different standardized densities to better understand the impact of fishing pressure. They particularly focused on social behaviours and their density‐dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that while behavioural traits such as high aggressiveness and less sociability are selected for by trawling independently of population density, the heritability of behaviours associated with fish activity and exploration change according to population density. These evolutionary responses can negatively impact social cohesion thus acting against evolved antipredator behaviours of grouping while maximizing the chances of more solitary fish to encounter predators (Crespel et al, 2021 ). Overall, Crespel et al showed that trawling adds other selective pressures to those exerted by mesh size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation